PERFORMANCE EVАLUАSI CONSULTАN DESIGN АNА PАDА JАLАN DАN JEMBАTАN PROJECTS IN GENERAL EMPLOYMENT DINАS DАN PENАTААN RUАNG KONBUTEN MАNGGАRАI YEAR 2020 - John Meo; Vivien Restianim (Jurnal Scientia, 2023)
In 2020 there were 56 project packages worked on by 7 (seven) planning consultants, 2 people from West Manggarai Regency and 5 people from Manggarai Regency. In planning, the work results are not maximized because they often rely on Google Maps in conducting surveys which are very different from the topographical conditions in the field. So that there are frequent changes in drawings, time or project duration and result in cost overruns. Meanwhile, in implementation, there are several consultants who do not have engineers according to their expertise, so it is difficult to read the drawings and choose local materials because they lack details for the specifications. The purpose of this study is to determine the influence of the quality of planning documents, planning time aspects, planning cost aspects and human resources on the performance evaluation of planning consultants. The method in this research is quantitative. The variables in this study are independent and dependent variables. The data used are primary and secondary data by distributing questionnaires to 18 respondents. From the results of the questionnaire data collection, the data was processed using the SPSS (Statistical Package for Social Science) version 24.0 computer. From the results of the questionnaire distributed to 18 respondents, it shows that the performance of the Manggarai District planning consultant in 2020 was good. The results of data analysis with multiple regression show that the independent variables simultaneously have a significant influence on the performance of the planning consultant with the test results F = 0.000 <0.05. The t test is obtained by the hypothesis of the mate from the vasts of the vasts. t = 20.887 > 2.120 for the planning time variable, sig t 0.000 < 0.05 and t = 16.910 > 2.120 for the planning cost aspect variable, sig t 0.000 <0.05 and t = 28.337 > 2.1200 for the human resource variable. The dominating variable is the human resources variable with a beta value of 0.283. The influence of the variable quality of planning documents, aspects of planning time, aspects of planning costs and human resources is 99.5%. The dominant influencing variable is the human resource variable with a beta value of 0.283. The results of the questionnaire distributed to 18 respondents in the field of Highways in Manggarai Regency concluded that the performance of the planning consultants was good.